Sociocultural project as communication with the city and citizens: from the experience of the Ekaterinburg Libraries - Cheremisinova, Irina; Rybakova, Olga (Managing of Culture, 2025)
The article is devoted to the consideration of the process of transformation of the role of modern municipal libraries in the context of digitalization of society and changes in social demands of citizens. In the context of rapid development of digital technologies, emergence of new forms of leisure and communication, as well as growing needs for informal education and self-development, libraries are forced to rethink their traditional functions and look for new ways of interaction with citizens. Using the example of Yekaterinburg Libraries, a model of building communications with the urban community through socio-cultural project activities is considered. Particular attention is paid to the role of libraries as socio-cultural hubs interacting with partners from business, education, culture and other spheres. Such cooperation allows to expand the range of services offered, attract additional resources, organize large-scale city events and projects, as well as introduce innovative forms of work with the population. Three new projects are analyzed: “Smart after-school care”, “University of informal education ‘Active seniors’ ” and “Workshop for schoolchildren ‘Masters of projects’ ”. The projects are developed taking into account the cultural and social needs of city residents, identified on the basis of a survey. They are also aimed at assisting in solving urgent problems facing the city. Thus, "Smart after-school care" offers intellectual leisure for children aged 7-12, not covered by organized leisure, "Active Seniors" is an educational program for the elderly, and "Project Masters" are creative workshops for teenagers. Thanks to the implementation of various projects, Yekaterinburg Libraries are able not only to perform traditional functions, but also to go beyond them, becoming platforms for informal education, creative development, exchange of experience and ideas. Thus, project activities allow them to satisfy a wide range of city residents' requests, which increases the social significance of libraries and helps to strengthen their ties with society.